2018
DOI: 10.1093/ntr/nty034
|View full text |Cite
|
Sign up to set email alerts
|

Alpha7 Nicotinic Receptors as Therapeutic Targets in Schizophrenia

Abstract: By examining alpha7 nicotinic receptor biology and recent efforts to target the receptor in clinical trials, it is hoped that investigators will be motivated to explore novel, promising directions focusing on the receptor as a strategy to treat cognitive symptoms in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 88 publications
1
51
1
2
Order By: Relevance
“…Our findings provide additional evidence that a nicotinebased treatment has the potential to improve attentional performance in a subgroup of predisposed subjects that show atypical patterns of low attentional or executive behaviour and differences in local integration of functional brain network topology. This finding may also be of relevance for other disorders such as mild cognitive impairment where a pilot trial on long term nicotine treatment resulted in improved attention, memory and psychomotor speed (Newhouse et al, 2012) or the treatment of cognitive dysfunction in patients with schizophrenia (Tregellas and Wylie, 2019).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Our findings provide additional evidence that a nicotinebased treatment has the potential to improve attentional performance in a subgroup of predisposed subjects that show atypical patterns of low attentional or executive behaviour and differences in local integration of functional brain network topology. This finding may also be of relevance for other disorders such as mild cognitive impairment where a pilot trial on long term nicotine treatment resulted in improved attention, memory and psychomotor speed (Newhouse et al, 2012) or the treatment of cognitive dysfunction in patients with schizophrenia (Tregellas and Wylie, 2019).…”
Section: Discussionmentioning
confidence: 74%
“…Previous clinical studies on the therapeutic use of nicotine and nicotinic agonists often failed to show a positive effect on cognition, attention and psychomotor functions in patients with neuropsychiatric disorders (Newhouse, 2019). Despite these failures in clinical studies, previous experimental results revealed significant nicotine effects on motor performance and attention (Heishman et al, 2010;Tregellas and Wylie, 2019). In addition, previous clinical studies documented an increased percentage of smokers in patients with a variety of psychiatric disorders, including attention-deficit hyperactivity disorder (ADHD) and schizophrenia (Pomerleau et al, 1995;Tregellas and Wylie, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los mecanismos que causan la disfunción de la ganancia de control incluyen la disfunción de los sistemas de NMDA y del GABA. Otros neurotransmisores que también están implicados en la (36) esquizofrenia, igualmente modulan el procesamiento visual . Por ejemplo, la deficiencia de dopamina ha sido ligada al daño en la respuesta perceptiva y electrofisiológica a las señales de (37,38) contraste…”
Section: Ganancia De Control E Integración En La Esquizofreniaunclassified
“…Nevertheless, differences in prescription patterns in smokers vs. nonsmokers cannot be exclusively attributed to differences in blood levels. Other factors, e. g., alteration in nicotinergic neurotransmission, that may be implicated in TRS have to be taken into account [13].…”
Section: Introductionmentioning
confidence: 99%